Epidemiology of binge eating disorder. Issue 6 (November 2018) - Erskine, Holly E.; Whiteford, Harvey A.
Abstract : Purpose of review: In 2013, binge eating disorder (BED) was officially recognized as a distinct eating disorder in the Fifth Edition of the Diagnostic and Statistical Manual of Mental Disorders. The purpose of this review is to assess the available epidemiological data to determine whether BED should be considered for inclusion in global disease burden quantification efforts, such as the Global Burden of Disease Study (GBD). Recent findings: A systematic search of three electronic databases (PubMed, EMBASE, and PsycINFO) found 32 studes meeting GBD inclusion criteria. The global pooled prevalence of BED was 0.9% (95% confidence intervals: 0.7–1.0%). Although women (1.4%, 1.1–1.7%) had higher prevalence than men (0.4%, 0.3–0.6%), no significant difference in prevalence was found between high-income countries (0.9%, 0.8–1.1%) and low- and middle-income countries (0.7%, 0.3–1.1%). Summary: The current article presents the findings of a recent systematic review of the epidemiology of BED and discusses the case for including BED as a new cause in future iterations of GBD. Abstract : Supplemental Digital Content is available in the text